Tmj Arthralgia: A Rarely Described Internal Joint Derangement And Characterization Regarding Factors Of Age , Pain Description, And Prevalence In Craniomandibular Disorders Individuals (CMDs) - Molina, Omar Franklin; Aquilino, Raphael Navarro; César, Ed Wilson; Cury, Sérgio Elias; Marçal, Ricardo Léllis; Miranda, Margarida M de (Cadernos UniFOA, 2017)
Aims: Characterize Craniomandibular Disorders (CMDs) and arthralgia individuals regarding factors of age, joint noises, frequency of burning pain and severity of pain. Material and Methods: 25 CMD and arthralgia patients, 39 CMDs and capsulitis patients were retrieved from a large sample of CMD patients and were compared with a control Non CMD group. History of sign and symptoms, questionnaires, clinical examination, description of pain, diagnostic tests and criteria for CMDs were used. Results: Mean age in the experimental (CMD+arthralgia group) was about 40.2 years old. The frequency of joint noises was about 72% in the CMDs+arthralgia group as compared to the other two control groups (56.4% and 40.6%) . Bilateral reciprocal click was also more frequently in the experimental group than in the controls and the difference was statistically significant. The frequency of severe pain was much higher in the CMD+arthralgia than in the CMD+capsulitis group (80% and 10.2% respectively). The description of burning pain was observed exclusively in the CMD+arthralgia group. Finally, the frequency of pain increased from the Non CMD to the CMD+capsulitis and to the CMD+arthralgia group. Conclusions: The results of this study indicate that arthralgia is a more chronic disorder characterized by burning pain, more severe pain and higher frequency of joint noises, specifically unilateral reciprocal click.